PERSEPSI MASYARAKAT DALAM PENANGGULANGAN BANJIR DI KECAMATAN LHOKSUKON: STUDI LITERATURE REVIEW - Akmal, Syaufi Nazmi; Shofiatun, Shofiatun; Kahar, Zamzam Nurfatiha (LPPM Universitas Malikussaleh, 2024)
The text discusses the recurring issue of flooding in North Aceh since 2019, with the most recent occurrence happening in October 2024. In July 2019, two villages in Lhoksukun were flooded, and since then, the phenomenon has persisted. A recent monitoring report reveals that on October 8, 2024, 7 villages were flooded, with water reaching a height of 60 cm. The purpose of this research is to investigate community perspectives and perceptions regarding flood disasters. The research utilizes the Systematic Literature Review (SLR) method to identify, review, and evaluate relevant studies in order to answer research questions. The findings indicate that the community in Lhoksukon Sub-district possesses good knowledge about preventing infectious diseases after a flood, with 48% of respondents demonstrating good knowledge and 92% expressing a positive attitude towards flood preparedness. The study recommends non-structural strategies involving community engagement and educational initiatives to increase awareness of infectious diseases after flooding, highlighting the effectiveness of video education compared to posters.